From targeted SCN1A analysis to whole exome sequencing: clinical utility and novel genetic findings in a Hungarian paediatric epilepsy cohort - Renata Szalai; Agnes Till; Krisztina Galimurka; Zsolt Banfai; Anna Zsigmond; Kinga Hadzsiev (Human Genetics, 2026)
Abstract Epilepsy represents a highly prevalent neurological disorder with a significant genetic component, particularly implicating ion channel genes, including SCN1A . In this study, 431 individuals with heterogeneous paediatric-onset epilepsy phenotypes were assessed at the Department of Medical Genetics, University of Pécs between 2018 and 2024. Genetic investigations employed Sanger sequencing, targeted epilepsy gene panels, whole exome sequencing, and multiplex ligation-dependent probe amplification for SCN1A copy number analysis. Thirty-six pathogenic or likely pathogenic SCN1A variants were identified, including 15 variants which have not been reported previously. Furthermore, 9 novel variants were detected in 12 additional epilepsy-associated genes. Diagnostic yield was proportional to the breadth of genomic interrogation. WES analysis revealed 6 novel variants in 19 genes. These findings underscore the considerable genetic heterogeneity of epilepsy and demonstrate the clinical utility of gene panels and WES, particularly in complex phenotypes. The identification of novel variants enhances molecular understanding and facilitates more precise genotype-phenotype correlations, reinforcing the value of comprehensive genomic diagnostics in epilepsy management.